Relationship of Ego Resilience, Perceived Social Support and Depression with Job Satisfaction of Working Women - Farhan, Sheeba; Atif, Tooba (Pakistan Journal of Applied Psychology (PJAP), 2022)
This study was aimed to explore the relationship of ego resilience, perceived social support and depression with job satisfaction of women working in different job sector (i.e. education, medicine, entrepreneur and others). After comprehensive literature review, it was hypothesized that there will be a positive relationship of ego resilience and perceived social support with job satisfaction, whereas there will be negative relationship of depression on job satisfaction. A sample of 135 working women was taken through purposive sampling technique. The age range of participants was between 25-50 years (Mean = 2.9, SD= 1.3). The measures, used in the study are: demographic information form, Ego Resilience Scale (ER89), Multidimensional Scale of Perceived Social Support (MSPSS), Center for Epidemiologic Studies Depression Scale-Revised (CESD-R-20), Minnesota Satisfaction Questionnaire (MSQ). Data were analyzed using SPSS (22.0). Correlation was conducted to find out the results. The study proved that ego resilience and perceived social support have a positive relationship with job satisfaction, whereas depression has a negative relationship with job satisfaction. Avenues for future research are open for different work settings including factors like ego resilience, perceived social support and depression among working women.